Institutionalizing inequality: field conditions, institutional belonging, and the distribution of identities - von Jacobi, N; Nicholls, A (Routledge, 2024)
The institutionalization of inequality represents an important research focus in various strands of the social sciences. Much theory has emerged within organizational studies and economic sociology, and within intersectionality research. However, there has, as yet been only limited work on the micro-processes by which institutions create and perpetuate inequality at the individual level. This article addresses this issue in terms of a new conceptual model that combines institutional theory on field conditions and Amartya Sen’s capability approach. We describe how inequality is institutionalized in terms of the distribution of identity positions and opportunities at the individual level. Specifically, we suggest that the institutionalization of inequality is a product of various types of institutional belonging that leads to (cumulated) disadvantaged identity positions for the individual. Our work connects Senian theory on conversion factors, multiple identities, and opportunity with established organization theory on fields and institutionalization processes to offer news insights into how patterns of inequality persist and may change.